The Antioxidative Role of Autophagy in Hearing Loss - Ye, Bin; Fan, Cui; Shen, Yilin; Wang, Quan; Hu, Haixia; Xiang, Mingliang (Frontiers in Neuroscience, 2019)
Autophagy, a highly conserved cellular mechanism, plays an essential role in the development and pathology of many central and peripheral nervous system diseases. The auditory system, especially hair cells (HCs) and spiral ganglion neurons (SGNs) in the inner ear, are postmitotic cells, which are extremely reliant on cellular homeostasis and energy supply. Therefore, autophagy may be involved in contributing to and facilitating the normal function of inner ear cells. Recently, studies on hearing loss induced by ototoxic drugs, noise exposure and other factors have revealed that autophagy could serve in an antioxidative capacity and could possess the potential to treat sensorineural hearing loss (SNHL). Therefore, here we review previous studies concerning autophagy and SNHL to gain insight into the role of autophagic mechanisms in inner ear disorders.